Going further post-RNA-seq: In silico functional analyses revealing candidate genes and regulatory elements related to mastitis in dairy cattle - Passe Pereira, Hyago; Lima Verardo, Lucas; Morena Del Cambre Amaral Weller, Mayara; Paula Sbardella, Ana [UNESP]; Prado Munari, Danísio [UNESP]; Morais De Paiva Daibert, Raquel; Araújo Carvalho, Wanessa; Antonio Machado, Marco; Fonseca Martins, Marta (Cambridge University Press (CUP), 2021)
This study aimed to obtain a better understanding of the regulatory genes and molecules involved in the development of mastitis. For this purpose, the transcription factors (TF) and MicroRNAs (miRNA) related to differentially expressed genes previously found in extracorporeal udders infected with Streptococcus agalactiae were investigated. The Gene-TF network highlighted LOC515333, SAA3, CD14, NFKBIA, APOC2 and LOC100335608 and genes that encode the most representative transcription factors STAT3, PPARG, EGR1 and NFKB1 for infected udders. In addition, it was possible to highlight, through the analysis of the gene-miRNA network, genes that could be post-transcriptionally regulated by miRNAs, such as the relationship between the CCL5 gene and the miRNA bta-miR-363. Overall, our data demonstrated genes and regulatory elements (TF and miRNA) that can play an important role in mastitis resistance. The results provide new insights into the first functional pathways and the network of genes that orchestrate the innate immune responses to infection by Streptococcus agalactiae. Our results will increase the general knowledge about the gene networks, transcription factors and miRNAs involved in fighting intramammary infection and maintaining tissue during infection and thus enable a better understanding of the pathophysiology of mastitis.
Keywords: Bovine; extracorporeal udders; mastitis; MicroRNA; transcription factors